Implementasi Pembelajaran Discovery Learning yang Terintegrasi Pendidikan Karakter dalam Pelajaran Biologi - Anis Sekarwati (Jurnal Pendidikan Edutama, 2020)
Abstract: The Background of this Classroom Action Research is the low motivation and student learning outcomes. This Classroom Action Research aims to find out the increased motivation and learning outcomes of students through Discovery Learning learning that integrates character education in learning biology on the subject of Living Classification. The design of this study is Classroom Action Research, consisting of 2 cycles, namely cycle I and cycle II. Each cycle consists of 3 meetings. This research approach is qualitative. The data analysis method is descriptive for both qualitative and quantitative data. The results showed that: 1) student learning motivation increased from cycle I by 75.40% to 81.59% in cycle II. 2) student learning outcomes increased from cycle I by 77.14% of students who completed learning increased to 88.57% in cycle II. Based on the data above that learning Discovery Learning model that is integrated with character education can increase student motivation and learning outcomes. The increase in the percentage of learning outcomes from cycle I to cycle II was 11.43% and the increase in learning motivation from cycle I to cycle II was 6.19%. Keyword: Motivation, Discovery learning, character education. Abstrak: Latar belakang Penelitian Tindakan Kelas ini adalah rendahnya motivasi dan hasil belajar siswa. Penelitian Tindakan Kelas ini bertujuan untuk mengetahui peningkatan motivasi dan hasil belajar peserta didik melalui pembelajaran Discovery Learning yang terintegrasi pendidikan karakter dalam pembelajaran biologi pokok bahasan Klasifikasi Makhluk Hidup. Desain Penelitian ini adalah Penelitian Tindakan Kelas, terdiri atas 2 siklus yaitu siklus I dan siklus II. Setiap siklus terdiri dari 3 kali pertemuan. Pendekatan Penelitian ini adalah kualitatif. Metode analisis datanya adalah deskriptif baik untuk data kualitatif maupun data kuantitatif. Hasil penelitian menunjukkan bahwa: 1) motivasi belajar siswa meningkat dari siklus I sebesar 75,40% menjadi 81,59% pada siklus II. 2) hasil belajar siswa meningkat dari siklus I sebesar 77,14% siswa yang tuntas belajar meningkat menjadi 88,57% pada siklus II. Berdasarkan data-data diatas bahwa pembelajaran model Discovery Learning yang terintegrasi pendidikan karakter dapat meningkatkan motivasi dan hasil belajar siswa. Kenaikan prosentase hasil belajar dari siklus I ke siklus II sebesar 11,43% dan kenaikan motivasi belajar dari siklus I ke siklus II sebesar 6,19%. Kata kunci: Motivasi, Discovery Learning, Pendidikan karakter